Spinodal decomposition in pure-gauge QCD - Krein, G. [UNESP] (AIP Publishing, 2005)
Spinodal decomposition in a model of pure-gauge SU(2) theory that incorporates a deconfinement phase transition is investigated by means of real-time lattice simulations of the fully nonlinear Ginzburg-Landau equation. Results are compared with a Glauber dynamical evolution using Monte Carlo simulations of pure-gauge lattice QCD. © 2005 American Institute of Physics.
Keywords: Color confinement; Ginzburg-Landau equation; Lattice QCD; Spinodal decomposition